Model-to-Model Transformation in Meta-Modeled CINCO Domains - Kuehn, Dennis (Electronic Communications of the EASST, 2018)
In this paper we present an approach to transform models of concrete domains specified with CINCO, a meta-modeling suite, into other CINCO domains. This procedure is demonstrated by transforming Webstory models to DIME applications. The model-to-model transformation increases benefits gained from domain-specific solutions, as shown with the DIME to web application generator, ultimately allowing for Webstories to be deployed and run as web applications.